Numerical simulation of flow over a static cylinder by using Lattice Boltzmann method - Zhang, Xin Fang (2017)
Lattice Boltzmann method (LBM) is a new numerical method used to compute fluid motion, which is the development of Lattice Gas Automata (LGA) in the 1980s. The main idea of LBM is to bridge the gap between micro-scale and macro-scale by not considering each particle behavior alone but behavior of a collection of particles as a unit. LBM has many advantages compared with the traditional numerical computing methods for fluid mechanics, such as, the simple algorithm, easy boundary treatment, etc. LBM has developed quickly on hydrodynamics calculations in recent years, and it is apparent that there is still a long way to go before LBM can achieve full engineering status. This paper focused on the numerical simulations of flows over single cylinder and multi-cylinder by using LBM method. Firstly, this paper discusses some comparisons between different Lattice Boltzmann models and boundary treatment schemes. Secondly, this paper introduces the investigations of the numerical models and boundary schemes for flows over static single cylinder and multi-cylinder. The traditional LBM models used in this paper are D2Q9 model, He-Luo model, D2G9 model, etc. The boundary conditions used in this paper are bounce-back scheme, OSIF and CPIF scheme, non-equilibrium extrapolation scheme, etc. Using different combinations, this paper compares the numerical simulations of the flow around static cylinder, such as the charts for lift and drag coefficients.